(untitled) (Multidisciplinary Journal of Science and Technology, 2023)
This article sheds light on the extent to which the owners of the musical arts and Fine Arts Sox are more susceptible to depression than other professional owners-his sabaps and solutions. Since art is associated with the psyche, it is easier for him to face problems. In this article you can see exactly how to proceed in these cases. Of course all sohaningham have cases of depression of their own difficulties but when it comes to music or the field of Fine Arts, this situation develops a lot faster.